If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = m(2) + b Reorder the terms for easier multiplication: 12 = 2m + b Reorder the terms: 12 = b + 2m Solving 12 = b + 2m Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. 12 + -1b = b + -1b + 2m Combine like terms: b + -1b = 0 12 + -1b = 0 + 2m 12 + -1b = 2m Add '-12' to each side of the equation. 12 + -12 + -1b = -12 + 2m Combine like terms: 12 + -12 = 0 0 + -1b = -12 + 2m -1b = -12 + 2m Divide each side by '-1'. b = 12 + -2m Simplifying b = 12 + -2m
| 2x^3+5x^2+20x+50= | | 6a+10=9a-6 | | 117=5x-8 | | 25x^2=400x | | 220650=175000+550x | | Y=4x+x-2 | | 300440=48*35x+35000 | | Y=3x+2x-4 | | h=-16t^2+36 | | h=-16x^2+36 | | 10X^2-2X-115=0 | | 8z-1=8 | | 4x^2=100x | | 9h-5=13 | | 6b-7=12b-19 | | (5x+3)(5x-1)= | | 17y-4=50-y | | 6(x-4)=7(x+2) | | 2(x+19)=13x+2(x^2-19) | | 9y^2-6y+5=0 | | 0.4+0.8(4)=0.5(y+4) | | y-15=3.50(x-0) | | 7h-16=47 | | (x-3)-(2x-7)+6=13(x-1)+4(2x+1)-7x | | 2(5x-4)-5(x-3)=2x-2(4-2x) | | 6x-4(-x+10)=x+41 | | 2(3x+4)=4(x-6) | | X=-3y+16 | | 3(x+6)+x=2(x+9)+2 | | -4.3-0.1(g)=-6.1 | | 10*0-6y=-60 | | 2ln(x+9)+3ln(5x+6)= |